Anticonvulsant activity 2-((5-(3-(4-fluorophenyl)-4-R2-1,2,4-triazole-3-yl)-thio)-1-arylethanone - O. A. Bihdan (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of work is to study of the anticonvulsant activity of 2-((5-(3-,4-fluorophenyl)-4-R2-1,2,4-triazole-3-yl)thio)-1-aryletanones, the establishment of some laws between the structure of compounds and their activity.